The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.1007/s00280-009-1053-2
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of 5-fluorouracil and the flavanoid oroxylin A on HepG2 human hepatocellular carcinoma and on H22 transplanted mice

Abstract: The anti-hepatocellular carcinoma effects in vitro and in vivo of 5-FU and oroxylin A combinations were synergistic and oroxylin A increased the sensitivity of HepG2 cells to 5-FU by modulating the metabolic enzymes of 5-FU and apoptotic-related proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Effective anti-tumor agents such as 5-fluorouracil (5-FU) often induce neutropenia, the most common side effect, followed by gastrointestinal toxicity [17], especially at the high dosage necessary to achieve anti-tumor efficacy. A series of cantharidin analogues were synthesized and screened for their anticancer potential in an attempt to achieve relatively low toxicity to normal cells [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Effective anti-tumor agents such as 5-fluorouracil (5-FU) often induce neutropenia, the most common side effect, followed by gastrointestinal toxicity [17], especially at the high dosage necessary to achieve anti-tumor efficacy. A series of cantharidin analogues were synthesized and screened for their anticancer potential in an attempt to achieve relatively low toxicity to normal cells [18,19].…”
Section: Resultsmentioning
confidence: 99%
“…Under normal circumstances, its production and resolution are in dynamic balance, and the redox state of the intracellular environment maintains a stable state. A great deal of research indicated that many antitumor drugs are closely related to the ROS initiation within tumor cells [19][20][21]. Such as antitumor drug arsenic trioxide (As 2 O 3 ), polysaccharides, quinone anticancer drugs, and so on, they can produce a lot of ROS inducing tumor cell apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Murine hepatoma 22 (H 22 ) cells were diluted with ice-cold 0.9% saline and inoculated subcutaneously at the right axilla of mice (5 ϫ 10 6 viable cells/ml) (Wang et al, 2008;Zhao et al, 2010). Twenty-four hours after inoculation, mice were divided randomly into 11 groups (with 10 mice/group): saline tumor control group; TNF-␣ 1.5 g/day group; LYG-202 750, 500, 250, and 125 mg/kg; LYG-202 750, 500, 250, and 125 mg/kg ϩ TNF-␣ combination group; and 10-hydroxycamptothecin 30 mg/kg group.…”
mentioning
confidence: 99%